2023
DOI: 10.3390/antibiotics12071216
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption/Desorption of Cationic-Hydrophobic Peptides on Zwitterionic Lipid Bilayer Is Associated with the Possibility of Proton Transfer

Abstract: Cell-penetrating peptides (CPPs) are short peptides built up from dominantly cationic and hydrophobic amino acid residues with a distinguished ability to pass through the cell membrane. Due to the possibility of linking and delivering the appropriate cargo at the desired location, CPPs are considered an economic and less invasive alternative to antibiotics. Besides knowing that their membrane passage mechanism is a complex function of CPP chemical composition, the ionic strength of the solution, and the membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
0
0
0
Order By: Relevance
“…The above suggests a modest interaction of electrostatic forces and the proposed peptide location on the water-lipid interphase. Pašalić and collaborators demonstrated that cationic peptides will sense electrostatic interactions with zwitterionic lipid groups and possibly adsorb on the outer leaflet depending on the lipid membrane composition, ionic strength, and peptide concentration [34].…”
Section: Discussionmentioning
confidence: 99%
“…The above suggests a modest interaction of electrostatic forces and the proposed peptide location on the water-lipid interphase. Pašalić and collaborators demonstrated that cationic peptides will sense electrostatic interactions with zwitterionic lipid groups and possibly adsorb on the outer leaflet depending on the lipid membrane composition, ionic strength, and peptide concentration [34].…”
Section: Discussionmentioning
confidence: 99%